(untitled) (Applied Biological Research, 2023)
In present study, a red macroalga Gracilaria edulis, collected from Rameshwaram Tamil Nadu (India) was used to extract sulfated polysaccharide by using cold acidic extraction method. The yield of sulfated polysaccharide was 2.35 g from 10 g dry powdered G. edulis. The extracted sulfated polysaccharide was analysed for antibacterial, anticancer, antioxidant and anticoagulant activities. The antibacterial activity of crude sulfated polysaccharide was examined on three pathogenic bacteria viz., Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus using well diffusion method. The zone of inhibition was 20 ± 0.05 mm in case of S. aureus, followed by E. coli and K. pneumoniae with zone of inhibitions of 15 ± 0.04 and 12 ±0.02 mm, respectively, at 50 μg mL-1sulfated polysaccharide. The anticancer activity was performed using HeLa cancer cell line and inhibitory concentration (IC50) was 57.1 μg mL−1 as per MTT assay method. The antioxidant activity was analysed by performing 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay and the inhibitory concentration (IC50) value of 174.62 μg mL-1 was observed. The anticoagulant assay was tested and partial thromboplastin time (PTT) increased by 4.5 sec at 40 μg mL-1 of sulfated polysaccharide using activated partial thromboplastin time (APTT) assay method.